PENGARUH LATIHAN PLYOMETRIC TERHADAP KECEPATAN LARI SPRINT PADA SISWA KELAS V DI SDN BONTORAMBA KECAMATAN PALLANGGA KABUPATEN GOWA - St. Mustainah; Ashar; M. Yusran Rahmat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of Plyometric Exercise on increasing sprint speed in fifth-grade students at Sdn Bontoramba, Pallangga District, Gowa Regency. The study used a quantitative approach with a One Group Pretest-Posttest Design. The research sample consisted of 33 fifth-grade students. Data collection techniques were carried out through observation, pretest, providing treatment in the form of plyometric exercises (zig-zag run), and posttest. Data were analyzed using descriptive statistics, Shapiro-Wilk normality test, and Wilcoxon Signed-Rank Test with the help of SPSS 27. The results showed that the average pretest score of 65.48 increased to 79.85 in the posttest. All students experienced an increase in results without any decrease in scores. The results of the Wilcoxon Signed-Rank Test showed a significance value <0.001, which means there is a significant effect of plyometric exercise on increasing students' sprint speed. Thus, plyometric exercise is proven to be effective as a physical education learning method to improve sprint speed abilities in elementary school students.